Effect of electrophoretic deposition of micro-quartz on the microstructural and mechanical properties of carbon fibers and their bond performance toward cement - Li, Huanyu; Liebscher, Marco; Ly, Khoa Hoang; Ly, Phong Vinh; Koeberle, Thomas; Yang, Jian; Fan, Qingyi; Yu, Minghao; Weidinger, Inez M.; Mechtcherine, Viktor (Journal of Materials Science, 2022)
An electrophoretic deposition (EPD) process of micro-quartz (MQ) powder is applied to carbon fibers (CFs) with the aim to enhance their interfacial bond to cementitious matrices and to investigate its influence on the microstructural and mechanical properties of the CFs itself. The electrophoretic mobility of the MQ particles with negative charge in aqueous media was confirmed by potential sweep experiments and zeta-potential measurements. High amounts of MQ were successfully deposited onto the fiber surface, as proven by scanning electron microscopy. Single-fiber tension tests and thermogravimetric analysis showed that EPD treatment had little impact on the tensile properties and thermal stability of the modified fibers. However, storing the CFs in cement pore solution impaired temperature stability of untreated and modified fibers. X-ray diffraction and Raman spectroscopy reveal specific changes of CF's microstructure upon EPD treatment and immersion in pore solution. Single-fiber pullout tests showed that the pullout resistance of MQ-modified CFs was enhanced, relative to untreated CFs. This augmentation can be explained by an enhanced interlocking mechanisms between CF and matrix due to the deposited quartz particles on the CF surface.
CRIS-Team Scopus Importer:2023-03-20